Prognostic value of legumain in uveal melanoma - WU, TONG (Mol Med Rep, 2016)
The present study aimed to assess the expression of legumain in uveal melanoma (UM) cell lines and primary UM specimens, and to determine the possible association between legumain expression and clinical as well as pathological characteristics to reveal its impact on the prognosis of patients with UM. Records of primary UM cases treated at Beijing Tongren Hospital and Tianjin Eye Hospital between 1996 and 2005 were retrieved for analysis and a total of 82 patients with uveal melanoma were included in the study. The expression of legumain in the formalin-fixed and paraffin-embedded surgical specimens of these 82 patients was determined using immunohistochemical analysis. In addition, the expression of legumain was examined in two uveal melanoma cell lines using polymerase chain reaction and western blot analyses. The association of legumain expression with clinical/pathological characteristics was analyzed using the χ(2) and Fisher's exact test. In addition, the impact of legumain on the prognosis of patients with uveal melanoma was examined. Upregulation of legumain was more predominant in the highly invasive uveal melanoma cell line MUM-2B compared with that in the MUM-2C with low invasiveness. Of 82 primary uveal melanoma tissues, 35 exhibited high expression of legumain, while the other 47 specimens exhibited low or negative expression of legumain. High legumain expression was primarily associated with local invasion of UM. Overall survival analysis revealed that the patients with high legumain expression exhibited poorer survival than patients with low/negative legumain expression. These findings suggested that upregulation of legumain is associated with malignant behavior of UM and that legumain may be used as an negative prognostic factor as well as a therapeutic target.